The Urgency of Water for Human life in Science and Al Quran Perceptive - Yankumara, Karana (http://jagadalimussirry.com/, 2020)
Abstract. Water being the most important component to life directness in the earth, especially for mankind. Water is not only used for physical needs but also used for spiritual purposes like a purification symbol in Islam. Islam requires its followers to perform ablution (using water) before performing prayers or reading the Al-Quran. In some regions, especially in Java, water is considered sacred because it is used to means of ritual. Water is also being the source of civilization. The water complexity for human life can’t be separated from the molecular components are compose it. Some of the medical research was found the water peculiarity as a potion. The another of water peculiarity famous as crystal structures, righteously human, water has an emotional. The water peculiarities were summarized in the Holy Quran and the Science development has given evidence that water is the great miracles Allah SWT has given to mankind, it is not a chance but it is a great management